2015
DOI: 10.1371/journal.pone.0122128
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Coping Style in the Relationship between Psychological Capital and Burnout among Chinese Nurses

Abstract: BackgroundBurnout is recognized as an occupational hazard, and nursing has a high risk of burnout. This study aims to explore the relationship between psychological capital (PsyCap) and burnout among Chinese nurses and the mediating role of coping style in this relationship.MethodsA total of 1,496 nurses (effective response rate: 80.11%) from two large general hospitals in Daqing City of China were selected as participants. Data were collected via the Chinese Maslach Burnout Inventory (CMBI), the psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
167
3
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(211 citation statements)
references
References 36 publications
13
167
3
8
Order By: Relevance
“…In nursing, burnout has been studied for several years because of its high prevalence and because it is recognized as an occupational risk (11) . In other studies that used MBI to identify burnout, a prevalence of 9.22%…”
Section: Discussionmentioning
confidence: 99%
“…In nursing, burnout has been studied for several years because of its high prevalence and because it is recognized as an occupational risk (11) . In other studies that used MBI to identify burnout, a prevalence of 9.22%…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some studies have confirmed the negative association between PsyCap and burnout in various professions such as school teachers (Cheung et al, 2011), bank employees (Li et al, 2015), or nurses (Ding et al, 2015); which suggests that having these psychological resources can help workers tolerating stressful situations or confront their demands at work without suffering chronic stress or burnout. Moreover, Laschinger and Fida (2014) conducted a two-wave survey with Canadian newly graduated nurses and found that nurses' PsyCap was related to both lower initial levels of burnout and lower increases in burnout after their first year of practice.…”
Section: Introductionmentioning
confidence: 87%
“…Also, coping styles are often viewed as mediating role (Liu, Kraines, Massing‐Schaffer, & Alloy, ; Nakano, ). A cross‐sectional study explored the mediating role of coping styles in the relationship between psychological capital and burnout among Chinese nurses (Ding et al., ). In addition, in China, most studies discussed the depression among patients with CAG from the point of Traditional Chinese Medicine (Kong Yanjun, ).…”
Section: Introductionmentioning
confidence: 99%